Diagnosis of gilbert's syndrome via pyrosequencing in clinical practice - L. I. Melnikova; L. Yu. Ilchenko; E. A. Dunaeva; M. V. Kozitsyna; O. P. Dribnokhodova; K. O. Mironov (SINAPS LLC, 2019)
Relevance. Gilbert's syndrome (GS) is a disease with an autosomal recessive type of inheritance caused by either impaired expression of the UGT1A1 gene, which encodes the isoform of the uridine-5-diphosphate glucuronosyltransferase (UDP-GTA1), or structural modifications of UDP-GTA1. GS is characterized by unconjugated hyperbilirubinemia; drug metabolism disorders and the development of drug-drug interactions. For diagnosis of GS, molecular biological methods are used to determine single nucleotide polymorphisms (SNP). Data on the prevalence of SNP related to GS in Russia are scarce. Study objective: Detection of genetic variant (TA)5/6/7/8 (rs8175347) in the UGT1A1 gene (Gilbert's syndrome) by pyrosequencing in outpatient practice.Material and methods: 200 outpatients were examined. Of whom: men - 107 (53.5 %), women - 93 (46.5 %) aged 15 to 86 years; patients from 30 years and older formed the majority - 175 (87.5 %). Detection of the genetic variant (TA)5/6/7/8 (rs8175347) in the UGT1A1 gene (GS) was carried out by pyrosequencing using the PyroMark AmpliSens® Pyroscreen UGT1A1 genetic analysis system (manufactured by the Federal Budgetary Scientific Institution Central Research Institute of Epidemiology of Rospotrebnadzor, Russia). For comparison, sequencing according to F. Sanger was used.Results: Normal (TA)6/(TA)6 genotype was found in 71 (35.5 %) patients, (TA)6/(TA)7 genotype was found in 81 (40.5 %) (heterozygous status) and (TA)7/(TA)7 genotype - in 48 (24 %) (homozygous status). Rare (TA)5/(TA)6, (TA)5/(TA)7, (TA)6/(TA)8 and (TA)7/(TA)8 genotypes were not found. The results of the determination of (TA)6/(TA)7 genotypes in the homo- and heterogeneous status by pyrosequencing and Sanger sequencing were the same in all cases. In 30 out of 48 patients, GS was newly diagnosed, and in half of the cases these patients were persons of the older group. None of them showed an increase in bilirubin level.Conclusion: The incidence of GS in outpatients was 24 %. Pyrosequencing allows us to identify various variants of the (TA)5/6/7/8 polymorphism in the homo- and heterozygous status. AmpliSens® Pyroscreen UGT1A1 kit can be used in clinical practice to diagnose GS and to assess side effects of prescribed drugs.